On inequalities of Kolmogorov-Hörmander type for functions bounded on a discrete net - Babenko, V. F.; Vakarchuk, M. B. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain a strengthened version of the Hörmander inequality for functions ƒ: ℝ → ℝ, in which, instead of ‖ƒ‖∞, we use the least upper bound of the values of f on a discrete set of points.